Label-free and sensitive detection of uracil-DNA glycosylase using exponential real-time rolling circle amplification - Xu, Yuan; Cui, Yun-Xi; Zhao, Qiu-Ge; Tang, An-Na; Kong, De-Ming (Analytical methods, 2018)
Sensitive evaluation of the uracil-DNA glycosylase (UDG) activity is greatly significant in both fundamental biochemical process studies and disease prognosis. In this study, a simple but sensitive UDG activity-sensing strategy was designed on the basis of UDG-triggered rolling circle amplification (RCA) reaction. In this strategy, two oligonucleotides were used. The hairpin-like structure of the oligonucleotide containing a uracil nucleotide is destroyed in the presence of UDG, and then can be employed to form the circular template of RCA and initiate the subsequent RCA reaction. The participation of a nicking endonuclease makes the RCA reaction proceed in an exponential amplification mode. The amplification product may fold into a G-quadruplex structure, which can be specifically combined with thioflavin T to generate a fluorescence signal without any extra label. This UDG activity-sensing strategy was demonstrated to work well in both end-point and real-time detection modes with high sensitivity and excellent specificity. As low as 5.5 × 10 −5 U mL −1 UDG could be detected. The advantages of simple operation, short RCA time and automatic measurement using commercial instruments make the real-time detection mode suitable for high-throughput detection with reduced risk of amplification product carryover contamination, and its application feasibility in real samples was demonstrated by UDG activity analysis of cell lysate.